A High Frequency Low Noise Acoustic STW VCO - Fleischmann, Bernd; Russer, Peter; Schaller, A.; Weigel, Robert (19th European Microwave Conference, 1989, 1989)
A voltage controlled oscillator (VCO) at 2.65 GHz has been developed using acoustic surface transverse wave (STW) delay lines operating at the fifth harmonic as the frequency controlling element. A filter with three transducers has been designed. The STW filter also serves as the oscillator output coupler. Compared to a microstrip coupler, the spectral characteristic of the oscillator is strongly improved due to the high selectivity of the transducer type coupler. The Q value and the untuned insertion loss of the filter were 3600 and 30 dB, respectively. A very thin metallization of only 25 nm aluminum was used for the STW filter. Excellent phase noise data have been measured. A single-sideband phase noise to carrier ratio of ¿93 dBc/Hz at 1 kHz and ¿63 dBc/Hz at 100 Hz was attained. As a phase shifter, a GaAs varactor diode circuit is used. Tuning range and output power of the oscillator were ± 375 kHz and 3 dBm, respectively. The load pulling (frequency stability) is ± 3.5 kHz at 12 dB return loss. Attenuation of harmonics is higher than 44 dB referred to the carrier.
–empty–::1512001600,fleischmann1989
Keywords: Acoustic noise; Acoustic transducers; Delay lines; Frequency; Microstrip; Phase noise; Power harmonic filters; Surface acoustic waves; Voltage control; Voltage-controlled oscillators